Migration and moult strategy of the curlew sandpiper - Barshep, Yahkat (Department of Biological Sciences, 2014)
The aim of this research is to describe the migration and moult strategies of the Curlew Sandpiper in relation to the different migratory routes and non-breeding areas of the species, focusing on the carry-over effects which conditions at the breeding grounds have on the timing of post-breeding migration and, subsequently, on the timing of moult at the non-breeding areas. Part of the study also describes the adaptive feature of moult in relation to migratory distance and environmental conditions at the non-breeding areas.